“The Gilded Cage”: Oppression Experienced by Upper-Class Women in Novel The Widows of Malabar Hill (2018) by Sujata Massey - Anastasya, Citra; Wahyuni, Delvi (Universitas Negeri Padang, 2023)
This analysis explores the issue of oppression towards women as a result of patriarchal practices, traditional traditions, gender roles, and social expectations in the novel The Widows of Malabar Hill (2018) by Sujata Massey. This is qualitative research that relies on text and applies feminist literary criticism to analyze the issue in the novel. This analysis aims to find out the forms of oppression experienced by the upper-class women in the novel. This research found that upper-class women experienced several forms of oppression including gender-based discrimination, gender-based marginalization, powerlessness, restricted access to formal education, restriction on property sales rights, being forbidden to work in public, limitation in freedom of mobility, cultural and religious practices, gender-based violence, and lack of legal rights. This research also indicates that even in the upper social classes, gender and patriarchal culture are the main causes of women's oppression. This oppression limits the opportunities that upper-class women have to develop their true potential.